THE PEDAGOGICAL EVALUATION OF THE RESPONSIVENESS OF PRE-SERVICE TEACHERS - Jurgena, Inese; Cēdere, Dagnija; Keviša, Ingrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
With the guidelines for pre-school education coming into effect, a paradigm change has occurred in Latvia, focusing on a child-centred educational process. Contradictions can be observed in the professional training of pre-school teachers. Clearly, pre-school educators ensure the transfer of values to the next generation and the stability of the system of education; nevertheless, their activity is often focused on imparting reproductive knowledge and skills and following familiar algorithms and stereotypes. The innovative trend – the development of child’s social and emotional skills – is not always dominant in the work of pre-school teachers. The aim of the research is to analyse the views of students, pre-service teachers, about teacher’s responsiveness in pedagogical activity. The research methods include the theoretical method – the analysis of theoretical literature, regulatory documents and academic studies - and the empirical method – surveys. The data have been processed with SPSS program. 247 full-time and part-time students of the University of Latvia participated in the study. The authors of the article concluded that pre-service teachers’ understanding of teacher’s responsiveness is sufficient. Most students are aware of the importance of teacher’s supportive reactions, responsibility and leadership in the regulation of child’s emotions. Pre-school teacher training plays an important role in the implementation of the social-emotional learning process, paying particular attention to raising students’ awareness of the role of emotions in the development of child’s self-regulation and the advancement of teachers’ skills in building positive and supportive relationships with children and parents.